Evaluating a public display installation with game and video to raise awareness of Attention Deficit Hyperactivity Disorder - Craven, Michael P.; Simons, Lucy; Gillott, Alinda; North, Steve; Schnädelbach, Holger; Young, Zoe (Springer International Publishing, 2015)
Networked Urban Screens offer new possibilities for public health education and awareness. An information video about Attention Deficit Hyperactivity Disorder (ADHD) was combined with a custom browser-based video game and successfully deployed on an existing research platform, Screens in the Wild (SitW). The SitW platform consists of 46-in. touchscreen or interactive displays, a camera, a microphone and a speaker, deployed at four urban locations in England. Details of the platform and software implementation of the multimedia content are presented. The game was based on a psychometric continuous performance test. In the gamified version of the test, players receive a score for correctly selected target stimuli, points being awarded in proportion to reaction time and penalties for missed or incorrect selections. High scores are shared between locations. Questions were embedded to probe self-awareness about ‘attention span’ in relation to playing the game, awareness of ADHD and Adult ADHD and increase in knowledge from the video. Results are presented on the level of public engagement with the game and video, deduced from play statistics, answers to the questions and scores obtained across the screen locations. Awareness of Adult ADHD specifically was similar to ADHD in general and knowledge increased overall for 93 % of video viewers. Furthermore, ratings of knowledge of Adult ADHD correlated positively with ADHD in general and positively with knowledge gain. Average scores varied amongst the sites but there was no significant correlation of question ratings with score. The challenge of interpreting user results from unsupervised platforms is discussed.